2023
DOI: 10.3390/plants12040909
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Screening of Antagonistic Endophytes against Phytophthora infestans and Preliminary Exploration on Anti-oomycete Mechanism of Bacillus velezensis 6-5

Abstract: Phytophthora infestans, the notorious pathogen of potato late blight, leads to a severe decline in potato yields and even harvest failure. We isolated 201 endophytic isolates from healthy root tissues of potatoes, among which 41 showed strong antagonistic activity against P. infestans. Further, the tolerance to stress and the potential application against potato late blight of these antagonistic isolates were tested. Most of them were extremely tolerant to stresses such as acid–alkali, temperature, UV, salt, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Comparative smBGCs exhibited a fascinating genetic potential to synthesize different chemical classes of bioactive secondary metabolites and undoubtedly indicated that the distribution patterns of smBGCs are mainly related to species phylogeny. Moreover, strain MEP2-6 T can produce endoglucanase, which is an important enzyme in plant-based biofuels and food-feed industries ( Behera et al., 2017 ), and is also a critical enzyme that inhibits Phytophthora infestans , a causative agent of potato late blight disease ( Zhang et al., 2023 ). Thus, we suggest that A. solani MEP2-6 T could be further investigated as a promising candidate for the discovery of novel bioactive compounds, biotechnological applications, and potato probiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative smBGCs exhibited a fascinating genetic potential to synthesize different chemical classes of bioactive secondary metabolites and undoubtedly indicated that the distribution patterns of smBGCs are mainly related to species phylogeny. Moreover, strain MEP2-6 T can produce endoglucanase, which is an important enzyme in plant-based biofuels and food-feed industries ( Behera et al., 2017 ), and is also a critical enzyme that inhibits Phytophthora infestans , a causative agent of potato late blight disease ( Zhang et al., 2023 ). Thus, we suggest that A. solani MEP2-6 T could be further investigated as a promising candidate for the discovery of novel bioactive compounds, biotechnological applications, and potato probiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Various B. velezensis and B. amyloliquefaciens strains have been reported as well-known biocontrol agents against bacterial, fungal, and viral plant pathogens such as Xanthomonas citri subsp. citri [72], Armillaria solidipes [73], Erysiphe heraclei [74], Phytophthora infestans [75], F. oxysporum f.sp. fragariae [76], F. oxysporum f.sp.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, various mechanisms of phytopathogen suppression by Bacillus strains have been actively studied [ 30 , 31 , 32 , 33 ]. In particular, chitinase and β-1,3-glucanase enzymes produced by B. velezensis CE 100 and the effectively lysing mycelium of Macrophomina phaseolina and Fusarium oxysporum f. sp.…”
Section: Discussionmentioning
confidence: 99%